The Aging Population and Dementia: The Need for Comprehensive Palliative Care - Jessica Marsigit; Valentine Natasya Moenardi; Rudi Putranto; Hamzah Shatri; Vinandia Irvianita; Edward Faisal (Acta Medica Indonesiana)
Dementia is a progressive condition that gradually impairs cognitive function, memory, and daily living skills. This disease not only impacts the individual but also has significant consequences for their families and caregivers. The global prevalence of dementia is on the rise, including in Indonesia. It's estimated that approximately 1.2 million people in Indonesia are currently living with dementia, a number projected to quadruple by 2050. Patients with dementia often experience a range of symptoms and complications, including pain, difficulty eating, shortness of breath, and susceptibility to infections. For those in advanced stages of the disease, family and caregivers play a crucial role in their well-being. However, this role can be emotionally taxing, making support essential. Palliative care offers a promising approach to enhancing the quality of life for both dementia patients and their families. By prioritizing symptom management, psychological support, and respecting patient autonomy, palliative care can help alleviate suffering and promote well-being throughout the disease's progression.